Memory for temporally dynamic scenes. Issue 7 (July 2017) - Ferguson, Ryan; Homa, Donald; Ellis, Derek
Recognition memory was investigated for individual frames extracted from temporally continuous, visually rich film segments of 5–15 min. Participants viewed a short clip from a film in either a coherent or a jumbled order, followed by a recognition test of studied frames. Foils came either from an earlier or a later part of the film (Experiment 1) or from deleted segments selected from random cuts of varying duration (0.5 to 30 s) within the film itself (Experiment 2). When the foils came from an earlier or later part of the film (Experiment 1), recognition was excellent, with the hit rate far exceeding the false-alarm rate (.78 vs. 18). In Experiment 2, recognition was far worse, with the hit rate (.76) exceeding the false-alarm rate only for foils drawn from the longest cuts (15 and 30 s) and matching the false-alarm rate for the 5 s segments. When the foils were drawn from the briefest cuts (0.5 and 1.0 s), the false-alarm rate exceeded the hit rate. Unexpectedly, jumbling had no effect on recognition in either experiment. These results are consistent with the view that memory for complex visually temporal events is excellent, with the integrity unperturbed by disruption of the global structure of the visual stream. Disruption of memory was observed only when foils were drawn from embedded segments of duration less than 5 s, an outcome consistent with the view that memory at these shortest durations are consolidated with expectations drawn from the previous stream.